Debt Maturity Structure and Credit Quality - Gopalan, Radhakrishnan; Song, Fenghua; Yerramilli, Vijay (Journal of Financial and Quantitative Analysis, 2014)
Abstract We examine whether a firm’s debt maturity structure affects its credit quality. Consistent with theory, we find that firms with greater exposure to rollover risk (measured by the amount of long-term debt payable within a year relative to assets) have lower credit quality; long-term bonds issued by those firms trade at higher yield spreads, indicating that bond market investors are cognizant of rollover risk arising from a firm’s debt maturity structure. These effects are stronger among firms with a speculative-grade rating and declining profitability, and during recessions.